The compilation of Qur’anic verses (juz 16 -30) and hadiths of sahih Muslim related to visual function - Md Halim, Siti Aishah; Badarudin, Noor Ezailina; Mohamad, Hasbullah (2018)
Al Quran and Al Hadith are not book of science, but books of Divine guidance which can be referred to inspire in understanding things including the scientific nature of creation. This study was performed to compile the Quranic verses (Juz 16-30) and Hadith of Sahih Muslim which are related to visual function with scientifically proven facts. Five keywords were chosen based on the process of seeing which were “light”, “eye/eyes” and “sight” and the synonyms of sight which were “vision” and “see”. Search engine, Search Truth was used to help gather the verses and hadiths comprising the keywords. Cross reference with the original copy of the Holy Quran and book of Sahih Muslim was done to ensure the authenticity of the Quranic verses and hadiths. Existing scientific facts regarding the revelation were then gathered to support the findings.There were 377 Quranic verses (Juz 16-30) containing the words “light”, “eye/eyes” and “sight” (and its synonyms). Out of this, only 6 Quranic verses have relation to visual function and have been scientifically proven. For hadith of Sahih Muslim, there were 1285 hadiths containing the words “light”, “eye/eyes” and “sight” (and its synonyms). Out of 1285 hadiths only 8 hadiths of Sahih Muslim found to have relation to visual function and has scientifically proven facts.